Pengaruh Model Pembelajaran CORE Terhadap Kemampuan Representasi Matematis Siswa Sekolah Dasar - Nourma Yunita; Siti Mariatul Qoriah (DIDAKTIKA, 2024)
The importance of mathematical representation skills that students need to possess motivates this research. The effective learning model to improve students' mathematical representation abilities is the CORE learning model. This study aims to determine the effect of the CORE learning model on students' mathematical representation abilities. The research method used is quasi-experimental, with the research design being the pretest-posttest control group design. The instrument used is a mathematical representation ability test. The data analysis technique used is inferential statistics by conducting a paired sample t-test. The results of the conducted research indicate that the CORE learning model has a significant impact on improving students' mathematical representation skills.